Consolidation in social change: women's alternative media in indonesia - Amelia, Diah; Amanah, Siti; Muljono, Pudji; Hapsari, Dwi Retno (Interaksi: Jurnal Ilmu Komunikasi, 2025)
Mainstream media shows a gap in engaging public participation, producing alternative content, and introducing social change. It is hoped that alternative media can be counter-hegemonic to mainstream media by providing a different perspective from the dominance of existing information. Women's alternative media can provide a voice and platform to empower women and place women's issues in their reporting. This study uses a critical paradigm with a qualitative approach and case study design. Researchers use the concepts of development communication, development journalism, and alternative media. The primary research subjects (informants) are the editors-in-chief or executive editors of five women's alternative media. The results of this study explain that women's alternative media contribute to the creation of a more inclusive and equitable space in society. They change negative narratives and stereotypes about women that frequently appear in mainstream media by creating more positive and accurate representations. They use creative and innovative ways to provide educational content about job skills, training, and self-development. They promote role models by featuring women's success stories in various fields. They interact directly with their communities to better connect with their audiences, understand their needs, and utilize digital platforms and social media to reach a wider audience.